Integrated teachings methods for entrepreneurship skills development studies: a case of one selected Multicultural Polytechnic College in Manicaland Province, Zimbabwe - Alex Marufu; Chakandinakira Unique; Dr. Chakandinakira Joseph (Globeedu Group, 2023)
The purpose of the research was to investigate the effect of various pedagogical styles that are adopted within a multicultural polytechnic college as means for lesson delivery to students. The study used the experiential model within the qualitative paradigm to explore how lecturers from a selected polytechnic college in Manicaland province would utilise various teaching methods at their disposal as they interact with students, as these lecturers convey the learned material. However, there was limited information on appropriate teaching methods that could be adopted to empower these students. The sample size for this study was one selected polytechnic college which was drawn from a targeted population of 10 polytechnic colleges in Zimbabwe. 30 students from the Entrepreneurship Skills Development (ESD) studies responded to open-ended questionnaires while 8 lecturers participated as key informants during the interviews. Findings from this study revealed that the teacher-centred approach which is largely the lecturer centred through using the lecture method had been widely employed by lecturers from Mut are Polytechnic College, with a minimum adoption of the student-centred approaches. The arguments raised for negating the student-centred approaches have been that there are time-consuming, require a lot of educational resources and students who are introverts and shy would not benefit effectively in the learning process. This research noted that the attitudes of both lecturers and students towards the use of various teaching methodologies in ESD studies have a bearing on the types of the didactic styles that are selected. Data from this study revealed that if effective teaching styles are adopted it would improve students’ attitude towards learning of ESD studies.